2011
DOI: 10.1016/j.bpj.2011.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Effects on NMDA Receptor Gating Kinetics

Abstract: Zinc accumulates in the synaptic vesicles of certain glutamatergic forebrain neurons and modulates neuronal excitability and synaptic plasticity by multiple poorly understood mechanisms. Zinc directly inhibits NMDA-sensitive glutamate-gated channels by two separate mechanisms: high-affinity binding to N-terminal domains of GluN2A subunits reduces channel open probability, and low-affinity voltage-dependent binding to pore-lining residues blocks the channel. Insight into the high-affinity allosteric effect has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 69 publications
5
68
1
2
Order By: Relevance
“…By fitting this model to single-channel data we determined that the change in NPA affinity between closed and open states is ∼5-fold, with NPA dissociation rate being 5-fold faster from open relative to closed receptors. However, given that this statedependency is relatively weak, with the change in free-energy being on the same scale with those previously reported for other NMDA receptor modulators (Amico-Ruvio et al, 2011, and also with the difference in free energy between N2A and N2B receptors Amico-Ruvio and Popescu, 2010), we anticipate that the magnitude of the NPA effects will vary substantially with experimental conditions that include such modulators and will also vary with the NMDA receptor isoform considered.…”
Section: Discussionsupporting
confidence: 60%
“…By fitting this model to single-channel data we determined that the change in NPA affinity between closed and open states is ∼5-fold, with NPA dissociation rate being 5-fold faster from open relative to closed receptors. However, given that this statedependency is relatively weak, with the change in free-energy being on the same scale with those previously reported for other NMDA receptor modulators (Amico-Ruvio et al, 2011, and also with the difference in free energy between N2A and N2B receptors Amico-Ruvio and Popescu, 2010), we anticipate that the magnitude of the NPA effects will vary substantially with experimental conditions that include such modulators and will also vary with the NMDA receptor isoform considered.…”
Section: Discussionsupporting
confidence: 60%
“…On the basis of these analyses, we conclude that ifenprodil-bound receptors had shorter openings on average because they spent more time in the low-activity gating mode; however, medium-and high-activity modes were still accessible and during these periods, openings were of a duration similar to those of ifenprodil-free receptors. This inhibitory mechanism was unexpected because it was not observed with zinc, which is also an NTD ligand (Amico-Ruvio et al, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…The recording pipette containing the excised membrane patch was positioned within one stream close to the interface, and the theta tube was mounted on a piezoelectric translator (Burleigh LSS-3100/3200) and used to exchange solution around the patch pipette. Open-tip potential measurements done at the end of each experiment showed that the 10 to 90% exchange occurred within 0.15 to 0.25 ms (Amico-Ruvio et al, 2011). Each barrel of the theta tube was connected to several solutions through a micro-manifold controlled with pinch valves (VC 6; Warner Instruments, Hamden, CT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14-17). [3], respectively]. Racemic ketamine had significant effects after the second and third dose (Fig.…”
Section: Experiments IImentioning
confidence: 93%